Pirates you don't know, and other adventures in the examined life : collected essays - Griswold, John (University of Georgia Press, 2014)
"Starting in 2005, John Griswold began publishing his nonfiction essays in Inside Higher Ed, McSweeney's Internet Tendency, Brevity, Ninth Letter, and Adjunct Advocate under the pen name Oronte Churm. This collection contains heavily revised previously published essays but much more new material covering a wide range of topics riffing on the writing life-from the utility of creative writing to babies, and from race issues in a university town to crocodiles. Griswold's tongue-in-cheek tone allows him to discuss this breadth of subject matter in an inviting and entertaining way while still addressing prevalent and important issues. Much of this book has to do with the tenuous and uncertain place of university adjuncts and other contingent instructors in the larger higher education ecosphere. Griswold writes, 'After more than a dozen years teaching creative writing, literature, and rhetoric at two universities, I fell into what they call the tenure stream at another school. The worries and stresses have changed, but my interests remain: What does it mean to be educated? To think, feel, write? To be whole? The writing in this book was my own attempt to see if I knew anything at all. And of course that's a lifelong journey, its rewards always temporary and therefore comic. Picture Long John Silver at the end of the movie, his dory filled with stolen gold, rowing and sinking; rowing, sinking, and gloating.'"--